Purchasing Decision Judging from Product Design, Product Quality, and Brand Image - Novita Ika Yuniarti; Eny Kustiyah (Almana : Jurnal Manajemen dan Bisnis, 2021)
The two-wheeler industry in Indonesia has a very positive trend. Advanced technology science as a means of smoothing the flow of communication and transportation, which causes very competitive competition. This study aims to test product design, product quality, the brand image on the purchase decision of a Mio motorcycle at a Yamaha Sumber Baru Dealer Rejeki Kartasura. The research sample was 70 consumers and used the multiple linear regression method. The results of product design, product quality, a brand image simultaneously and partially have a significant effect on the purchase decision of the Mio Motor at Yamaha Sumber Baru Dealer Rejeki Kartasura. Three independent variables can explain the purchase decision.